2014
DOI: 10.1016/j.neuron.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Ascending SAG Neurons Control Sexual Receptivity of Drosophila Females

Abstract: Mating induces pronounced changes in female reproductive behavior, typically including a dramatic reduction in sexual receptivity. In Drosophila, postmating behavioral changes are triggered by sex peptide (SP), a male seminal fluid peptide that acts via a receptor (SPR) expressed in sensory neurons (SPSNs) of the female reproductive tract. Here, we identify second-order neurons that mediate the behavioral changes induced by SP. These SAG neurons receive synaptic input from SPSNs in the abdominal ganglion and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
229
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(240 citation statements)
references
References 57 publications
11
229
0
Order By: Relevance
“…Other recent studies have also examined the abdominal ganglion neurons necessary for female reproductive behavior in Drosophila (18,19,(33)(34)(35). One question is whether the neurons we report here are the same or different from those previously reported.…”
Section: Resultssupporting
confidence: 41%
See 1 more Smart Citation
“…Other recent studies have also examined the abdominal ganglion neurons necessary for female reproductive behavior in Drosophila (18,19,(33)(34)(35). One question is whether the neurons we report here are the same or different from those previously reported.…”
Section: Resultssupporting
confidence: 41%
“…One question is whether the neurons we report here are the same or different from those previously reported. Gou et al (33) focused on ascending neurons from the reproductive tract, and both Feng et al (34) and Bussell et al (35) reported stimulation of neurons favoring receptivity. In contrast, we observed that stimulation of R17H01-GAL4 neurons inhibits receptivity, suggesting the neurons examined here differ from the ones reported above.…”
Section: Resultsmentioning
confidence: 99%
“…For example, virgins are receptive to male courtship and lay very few eggs, whereas mated females are unreceptive to courtship, lay eggs frequently, and preferentially consume proteins over sugars (Carvalho et al, 2006; Kubli, 2003; Ribeiro and Dickson, 2010). Much progress has been made in recent years in elucidating the molecular and circuit basis by which the experience of mating modifies physiologies and behaviors of female flies (Bussell et al; Feng et al, 2014; Häsemeyer et al, 2009; Rezával et al, 2012; Yang et al, 2009; Zhou et al, 2014). In contrast, whether and how egg-laying need influences how female flies interpret the valence of external stimuli – so as to guide their decision of whether to move towards or away from specific stimuli – remains little explored, despite the fact that female flies are known to be highly selective about where to lay eggs (Azanchi et al, 2013; Dweck et al, 2013; Joseph et al, 2009; Joseph and Heberlein, 2012; Rockwell and Grossfield, 1978; Schwartz et al, 2012; Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral genetic studies of Drosophila have identified critical brain neurons that regulate female sexual behavior (Ferveur, 2010). Electrical silencing of SAG neurons of the abdominal ganglion inhibits female sexual receptivity (Feng et al, 2014). Similarly, inactivation of subsets of doublesex-expressing brain neurons (pCd and pC1) also inhibits female sexual receptivity (Zhou et al, 2014).…”
mentioning
confidence: 99%